Role of neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio as prognostic markers in oral cavity cancers - Akshat Malik; Aseem Mishra; Manish Mair; Swagnik Chakrabarti; Apurva Garg; Hitesh Singhvi; Prashant Chopda; Burhanuddin Qayyumi; Nupoor Sawarkar; Yash Mathur; Rathan Shetty; Sudhir Nair; et al. (Indian Journal of Medical and Paediatric Oncology)
Background: Various studies have associated inflammation with carcinogenesis. But still, the role of inflammatory markers in oral cancer has not been evaluated extensively. Most of the existing studies have been done on patients of varied sites, and their sample size is also scarce. In this study, we have evaluated the impact of neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) on various clinicopathological factors and survival. Methodology: This was a retrospective analysis of prospectively collected data of 400 patients with oral squamous cell cancer. The pretreatment neutrophil and lymphocyte and platelet counts were recorded, and NLR and PLR were calculated for all patients. The NLR and PLR tertiles were correlated with the incidence of various clinicopathological factors and overall survival. Results: The median follow-up of the cohort was 36 months. The mean survival of the cohort was 41.7 months. PLR was associated with higher incidence of adverse clinicopathological factors. There was a trend of decreased overall survival with increasing NLR tertile. It was found to be significant only for the group which received adjuvant chemoradiotherapy (P 0.01). Patients with higher PLR values have been found to have a lower overall survival (P 0.006). Conclusion: NLR and PLR can be used to predict survival and outcomes in patients oral cavity cancer. PLR is a good predictor for adverse clinicopathological factors and survival. NLR can predict survival only in the subset of patients who have received chemotherapy.